2000
DOI: 10.1002/1097-4636(200011)52:2<308::aid-jbm9>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of isostatic compression on the stability of vancomycin loaded with a calcium phosphate-implantable drug delivery device

Abstract: It is essential to prevent microbial infections after osteoarticular trauma or prosthesis implantation. As an alternative to antibiotic parenteral administration, antibiotic-loaded biomaterials allow high concentrations to be obtained in situ without systemic toxicity. Although the formulation of biphasic calcium-phosphate (BCP)-vancomycin granules by isostatic compression has recently been used to produce drug-delivery devices, the stability of vancomycin needs to be proven. In this study, vancomycin was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…For BCP, minor phases of HA and β‐TCP, and α‐TCP were present. As has been used in a number of recent studies, the HA/β‐TCP peak ratios were estimated using the simple peak height law,35–38 where the HA/β‐TCP ratio was found to be approximately 61% HA using where I 100,HA and I 100β‐TCP are the intensities of the maximum intensity peaks of HA and β‐TCP, respectively 35. XRD analysis of the Group IV OB‐seeded samples (after mechanical testing) showed that the BCP discs in Group IV were only 53%, with an error of ± 7 to 10% HA 35.…”
Section: Resultsmentioning
confidence: 99%
“…For BCP, minor phases of HA and β‐TCP, and α‐TCP were present. As has been used in a number of recent studies, the HA/β‐TCP peak ratios were estimated using the simple peak height law,35–38 where the HA/β‐TCP ratio was found to be approximately 61% HA using where I 100,HA and I 100β‐TCP are the intensities of the maximum intensity peaks of HA and β‐TCP, respectively 35. XRD analysis of the Group IV OB‐seeded samples (after mechanical testing) showed that the BCP discs in Group IV were only 53%, with an error of ± 7 to 10% HA 35.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the experimental conditions of orthogonal test scheme to prepare microspheres, the concrete steps are as follows: particle size of 500 microspheres in each group was measured , and then to calculate the average particle size d (particle size was measured by the optical microscope); 500 microspheres in each group were extracted to count the number of adhesion microspheres N, according to the formulas (3)-(5) to calculate S1, S2, S3, and then according to the formula (6) to calculate the total S, the results are shown in Table 3.…”
Section: Preparation Of Gelatin Microspheresmentioning
confidence: 99%
“…The pH of the solution was then adjusted to 9.5 by adding NH 4 OH and water in a 1 : 1 ratio. A stoichiometric amount of 1 M (NH 4 ) 2 HPO 4 solution was added to the above mixture and the precipitated mixture of phosphates was dissolved by adding concentrated HNO 3 until the pH became 1.…”
Section: Synthesismentioning
confidence: 99%
“…Because of its biocompatibility and osteoconductive [1] properties, it has many biological applications including as a bone graft substitute [2,3], a sustained-release drug delivery device [4] and for protein purification. However, biological apatite differs from pure and synthetically produced calcium hydroxyapatite (HAP) in terms of stoichiometry, composition, crystallinity and other physical and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%